Amylolytic ability of bacteria isolated from termite (Coptotermes sp.) gut - Putri Dwi Mulyani; Radhiyah Mardhiyah Hamid; Rifqi Zahroh Janatunaim; Yekti Asih Purwestri (Indonesian Journal of Biotechnology, 2018)
BSR 2, BSR 3, BSR 8, and BSR 9, different bacteria isolated from the termite gut, have been shown to possess cellulolytic activities, but their amylolytic ability has heretofore been unknown. This study attempted to fill in this knowledge gap. The formation of a clear zone using the iodine test showed that the bacteria were able to produce and secrete amylase. Based on the results, the best cultivation times for strains BSR 2, BSR 3, BSR 8, and BSR 9 were 6, 3, 2, and 2 d, respectively, yielding amylase activities of 2.59 ± 0.13 U/mg, 2.00 ± 0.08 U/mg, 1.67 ± 0.10 U/mg, and 1.55 ± 0.12 U/mg, respectively. BSR 2 had the highest amylase activity compared with the other bacterial isolates. The optimum ph for bacterial amylase activity of BSR 2 was 7.0, and the optimum temperature was 40°C. The molecular characterization of isolates BSR 2, BSR 3, BSR 8, and BSR 9 was based on 16S rRNA gene sequences. Isolates BSR 8 and BSR 9 were thus identified as Brevibacillus parabrevis and Brevibacillus sp. With similarities amounting to 92.48% and 95.91%, while the BSR 3 isolate was identified as Pseudomonas alcaligenes with a similarity of 94.29%, and the BSR 2 isolate could not be identified yet.